IMMUNOHISTOCHEMICAL EXPRESSION OF CYCLIN D1 IN CONVENTIONAL SQUAMOUS CELL CARCINOMA OF ORAL CAVITY - Manal Rauf,; Henna Azmat ,; Sumaiya Shahab,; Ahson Ahmad,; Shafaq Khadija,; Javeria Firidi, (Journal of Ayub Medical College Abbottabad, 2023)
Background: Oral squamous cell carcinoma (OSCC) is the most common malignant neoplasm of the oral cavity, the incidence of which has significantly increased in the last 10 years. In Pakistan, it is reported to be the most common cancer among men and the second most common in women. Cyclin D1 is a protein involved in cell cycle regulation from G1 phase to S phase. Down regulation of this molecule causes inhibition of cell cycle transition and may lead to carcinogenesis. We studied the expression of Cyclin D1 in biopsies of oral squamous cell carcinoma to evaluate the staining patterns in various grades and sites of the oral cavity. Cyclin D1 was expressed in 53.8% cases of OSCC and showed a significant association with tumour differentiation, with higher intensity staining seen in poorly differentiated cases of OSCC. Thus, Cyclin D1 can be regarded as a marker of malignant potential of OSCC and can help identify cases with poorer outcome.